2020
DOI: 10.1016/j.ebiom.2020.102911
|View full text |Cite
|
Sign up to set email alerts
|

Linear B-cell epitopes in the spike and nucleocapsid proteins as markers of SARS-CoV-2 exposure and disease severity

Abstract: Background Given the unceasing worldwide surge in COVID-19 cases, there is an imperative need to develop highly specific and sensitive serology assays to define exposure to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Methods Pooled plasma samples from PCR positive COVID-19 patients were used to identify linear B-cell epitopes from a SARS-CoV-2 peptide library of spike (S), envelope (E), membrane (M), and nucleocapsid (N) structural proteins by peptide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
183
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 39 publications
16
183
1
2
Order By: Relevance
“…As a consequence, our study predicted several B cell epitopes that were in line with those identified by Grifoni et al (Table S2). Additionally, one of the predicted B-cell epitope from amino acid residues 154-166 was in agreement with the study from Amrun et al (Table S2) [74]. Moreover, several studies have reported the characterization of B-cell epitopes from the N protein of many viruses from humans and animals [23,[75][76][77].…”
Section: Discussionsupporting
confidence: 90%
“…As a consequence, our study predicted several B cell epitopes that were in line with those identified by Grifoni et al (Table S2). Additionally, one of the predicted B-cell epitope from amino acid residues 154-166 was in agreement with the study from Amrun et al (Table S2) [74]. Moreover, several studies have reported the characterization of B-cell epitopes from the N protein of many viruses from humans and animals [23,[75][76][77].…”
Section: Discussionsupporting
confidence: 90%
“…We previously developed an ELISA-based serological assay based on the four immunodominant IgG linear epitopes on the S and N proteins. 21 To capture a wider repertoire of antibodies against the S protein, in this study we developed a flow cytometry assay based on the full-length S protein. The assay is more time efficient; results are available within 2 h. The assay is also well suited to detect anti-S protein antibodies in symptomatic and asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Demographic data, clinical and laboratory parameters during the hospitalisation period were retrieved from patient records ( Table S1 ). 21 Whole blood of patients was collected into BD Vacutainer® CPT tubes and centrifuged at 1700 g for 20 min to obtain plasma fractions. Plasma samples were categorised according to three time points: median 5 days post-illness onset (pio), median 10 days pio, and median 23 days pio.…”
Section: Methodsmentioning
confidence: 99%
“…Full-length recombinant antigens, however, in addition to high costs and storage constraints, may suffer from stability problems, batch-to-batch variations and in some cases may give rise to cross-reactivity leading to ambiguous detection outcomes. This might be the case for SARS-CoV-2 when using proteins sharing high homology with genetically similar, co-circulating, human coronaviruses (hCoV) that are responsible for common cold [ 6 , 7 ]. Studies towards fine dissection of the specific regions on the viral proteins recognized by virus-specific antibodies have been recently published focusing on the S protein [ 6 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%